2020
DOI: 10.3390/su12072593
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–Temporal Evolution of Urban Resilience and Its Influencing Factors: Evidence from the Guanzhong Plain Urban Agglomeration

Abstract: Rapid urbanization places great pressure on the ecological environment and the carrying capacity of cities. Improving urban resilience has become an inherent requirement for the sustainable development of modern cities and urban agglomerations. This study constructed a comprehensive system to evaluate urban resilience from four perspectives: The ecological environment, economic level, social environment, and infrastructure services. As a case study, the extreme entropy method and panel data from about 16 citie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Firstly, through the measurement of the resilience level of the cities in the study area, this study finds that the level of economic resilience and social resilience is the key to determining the overall resilience level of the city. This confirms the research of Zheng et al (2018) [57] and Ma et al (2020) [58], arguing that economic and social levels are the main determinants of urban resilience. Cities with higher economic and social levels have relatively large resource investment in improving the level of urban resilience, making their level of urban resilience relatively high.…”
Section: Theoretical Contributionsupporting
confidence: 89%
“…Firstly, through the measurement of the resilience level of the cities in the study area, this study finds that the level of economic resilience and social resilience is the key to determining the overall resilience level of the city. This confirms the research of Zheng et al (2018) [57] and Ma et al (2020) [58], arguing that economic and social levels are the main determinants of urban resilience. Cities with higher economic and social levels have relatively large resource investment in improving the level of urban resilience, making their level of urban resilience relatively high.…”
Section: Theoretical Contributionsupporting
confidence: 89%
“…From the conceptual point of view, most domestic and foreign scholars define the concept of urban spatial resilience in terms of urban systems absorbing shocks and attenuating disturbances. To be more precise, they focus on spatial attributes of urban systems as a material form possessed by cities, broadening the understanding of urban space in complex social-ecological systems [18][19][20][21][22][23]. In terms of research content, scholars at home and abroad have attempted to construct indicator systems with specific entry points, which include urban road traffic [6], local urban space [24][25][26][27][28][29][30], and multiscale urban resilience constructions [31].…”
Section: Introductionmentioning
confidence: 99%
“…Martin, Zhou et al and Rose et al all constructed an indicator system of economic resilience from the perspective of economic shocks (Martin and Gardiner, 2019;Rose, 2004;Zhou et al, 2020); Abdul et al set up a social resilience indicator system to enhance disaster management (Abdul Majeed et al, 2018;Abdul Majeed et al, 2020;Cutter et al, 2008). Nevertheless, some other scholars have established an inclusive system for evaluating urban disaster resilience from the four aspects: Ecological environment, Economy, Society and Infrastructure services (Ma et al, 2020). Through above analysis, we found that scholars had constructed UR analysis framework from five aspects: Economy, Society, Infrastructure, Ecology and Disasters, these dimensions were decided by the characteristics of the research objects.…”
Section: Introductionmentioning
confidence: 99%